STEAM EDUCATION SYSTEM AND TEACHING FOREIGN LANGUAGES WITH IT.: STEAM EDUCATION SYSTEM AND TEACHING FOREIGN LANGUAGES WITH IT. - G'aniyeva, Hayriniso; Abdurahmonova, Umida; Amirova, Lobar (Maktabgacha taʼlim jurnali, 2022)
This article provides information on what the STEAM education system is and its functions, effectiveness, and in what areas of education it can be used. It goes on to give a brief overview of the consequences of teaching foreign languages in this education system.